Effect of Electrical Impedance Tomography-Guided Early Mobilization in Patients After Major Upper Abdominal Surgery: Protocol for a Prospective Cohort Study - Song, Xuan; Yang, Daqiang; Yang, Maopeng; Bai, Yahu; Qin, Bingxin; Tian, Shoucheng; Song, Gangbing; Guo, Xiuyan; Dong, Ranran; Men, Yuanyuan; Liu, Ziwei; Liu, Xinyan; et al. (Frontiers in Medicine, 2021)
ABSTRACT Background Pulmonary complications are common in patients after upper abdominal surgery, resulting in poor clinical outcomes and increased costs of hospitalization. Enhanced Recovery After Surgery Guidelines strongly recommend early mobilization postoperatively; however, the quality of the evidence is poor, and indicators for quantifying the effectiveness of early mobilization are lacking. This study will evaluate the effectiveness of early mobilization in patients undergoing an upper abdominal surgery using electrical impedance tomography (EIT). Specifically, we will use EIT to assess and compare the lung ventilation distribution among various regions of interest (ROI) before and after mobilization in this patient population. Additionally, we will assess the temporal differences in the distribution of ventilation in various ROI during mobilization in an effort to develop personalized activity programs for this patient population. Methods In this prospective, single-center cohort study, we aim to recruit 50 patients after upper abdominal surgery between July 1, 2021 and June 30, 2022. This study will use EIT to quantify the ventilation distribution among different ROI. On postoperative day 1, the nurses will assist the patient to sit on the chair beside the bed. Patient's heart rate, blood pressure, oxygen saturation, respiratory rate, and ROI 1-4 will be recorded before the mobilization as baseline. These data will be recorded again at 15 min, 30 min, 60 min, 90 min, and 120 min after mobilization, and the changes in vital signs and ROI 1-4 values at each time point before and after mobilization will be compared. Ethics and dissemination The study protocol has been approved by the Institutional Review Board of Liaocheng Cardiac Hospital (2020036). The trial is registered at chictr.org.cn with identifier ChiCTR2100042877, registered on January 31, 2021. The results of the study will be presented at relevant national and international conferences and submitted to international peer-reviewed journals. There are no plans to communicate results specifically to participants. Important protocol modifications, such as changes to eligibility criteria, outcomes, or analyses, will be communicated to all relevant parties (including investigators, Institutional Review Board, trial participants, trial registries, journals, and regulators) as needed via email or in-person communication.